User-Centric Security Education and Awareness for Web Users - Thandy Simanjuntak (Geviva Publisher, 2023)
In an era marked by ubiquitous digital interactions, the security of web users becomes paramount in safeguarding sensitive information and mitigating the risks associated with cyber threats. This research addresses the problem of the persistently high incidence of online security breaches, often attributed to inadequate user awareness and education. The study aims to investigate the effectiveness of user-centric security education and awareness programs in enhancing the online safety practices of individuals, ensuring they are equipped with the necessary knowledge and skills to protect their personal information and navigate the digital landscape securely. The research problem centers around the need to understand how various user demographics respond to different forms of security education, the retention of knowledge over time, and the potential influence of corporate culture on individuals' security practices. Source: This paper examines the role and value of information security awareness efforts in defending against social engineering attacks. It categorizes the different social engineering threats and tactics used in targeting employees and explores approaches to defend against such attacks. The research aims to determine the effectiveness of user-centric security education and awareness programs in mitigating social engineering attacks by categorizing different threats and tactics used to target employees. To address the persistent issue of online security breaches and the lack of user awareness and education, this research aims to investigate the effectiveness of user-centric security education and awareness programs in enhancing the online safety practices of individuals. The research problem focuses on understanding how different user demographics respond to various forms of security education, the retention of knowledge over time, and the potential impact of corporate culture on individuals' security practices.